Digital footprint and awareness: cyber hygiene education in public education - Petrecki Krisztofer; Dorovtsi Adam; Daróci Ádám; Доровці Адам (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. With the ubiquity of internet use among youth – about half of 8–17 year-olds reportedly go online daily – concerns have grown over issues like privacy, cyberbullying, and exposure to cyber threats [1]. Paradoxically, many young people are tech-savvy yet lack awareness of their own digital footprints and how to manage them [1]. The cyber hygiene concept encompasses the safe and responsible online practices needed to protect one’s digital identity and security. As internet technologies become deeply ingrained in daily life, the security problems associated with poor cyber hygiene and unmanaged digital footprints (e.g. personal data leaks, reputation damage) have become a frequent topic of concern. This has underscored the importance of educating the general public – especially students – about managing their digital footprints and practicing good cyber hygiene from an early age. Educating students about cybersecurity and digital citizenship is widely seen as critical for mitigating online risks. Experts emphasize that user education and awareness are crucial to creating a safer cyber environment [2]. For example, Subaşı et al. (2023) examined teenagers’ awareness of digital footprints and found significant gaps: students who spent more time online (e.g. 4–6 hours daily) actually tended to have lower understanding of their digital footprints than those online less often [3]. Such findings suggest that simply growing up as “digital natives” does not guarantee wisdom about online privacy or safety. Formal cyber hygiene education in schools can bridge this gap by teaching students about personal data protection, safe communication, and the long-term implications of their online actions. Research also shows this need extends to those guiding children: Buchanan et al. (2019) found that while parents and teachers are very aware of digital footprint risks and cyber-safety issues, they often lack knowledge on how to help children manage their online presence and leverage positive opportunities [4]. This highlights the need not only for student training but also for resources and training for educators to effectively teach cyber hygiene.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: digital footprint; cyber hygiene; cybersecurity education; privacy awareness